Pelatihan Tata Kelola Organisasi Majelis Taklim At-Taqwa Kampung Korem Biak Utara - Hermanu Iriawan; Edyanto Edyanto (Jurnal Informasi Pengabdian Masyarakat, 2026)
Majelis taklim is one of the non-formal Islamic educational institutions that has a strategic role in increasing religious understanding, building social solidarity, and strengthening community capacity. However, in its implementation, many taklim assemblies still face various obstacles in the aspect of organizational governance, such as the lack of a clear division of duties, unorganized administration, and weak work program planning. This Community Service (PkM) activity aims to increase the capacity of the management of the Attaqwa Taklim Council of Korem Village, North Biak District, Biak Numfor Regency in effective and sustainable organizational management. The methods used include counseling, training, and participatory discussion. The activity was carried out by involving the management and members of the taklim council as the main participants. The results of the activity showed an increase in participants' understanding of the principles of organizational governance, the preparation of a clearer organizational structure, the division of tasks and management functions, and the preparation of annual work programs. In addition, participants also acquire basic skills in organizational administration and management of religious activities. This activity made a positive contribution to the institutional strengthening of the Attaqwa Taklim Council as a forum for the development of the people in Korem Village. Therefore, continuous assistance is needed to ensure the implementation of good organizational governance in supporting the sustainability of the taklim assembly program.